Linking integrated reporting quality with sustainability performance and financial performance in South Africa - van der Lugt, Cornelis T.; Mans-Kemp, Nadia (South African Journal of Economic and Management Sciences, 2020)
Background: Ten years have elapsed since the launch of the International Integrated Reporting Council. Stakeholders increasingly question whether integrated reporting (IR) meets the objectives of decision-usefulness and accountability.Aim: The primary objective of this study was to assess the usefulness of IR by examining the interrelations between the integrated reporting quality (IRQ), sustainability performance and financial performance of listed companies in South Africa.Setting: The study is conducted in the country where integrated reporting is most established. The links between the IRQ of the Top 100 companies listed on the Johannesburg Stock Exchange and their environmental, social and corporate governance (ESG) scores and multiple financial indicators are investigated over the period 2013-2018.Methods: The EY Excellence in Integrated Reporting Awards was used as a metric to determine the sample companies' IRQ. These awards were ranked according to four categories, namely 'progress to be made', 'average', 'good' and 'excellent'. Sustainability (ESG scores), as well as financial performance data (accounting-based and market-based variables) were sourced from Bloomberg. The panel data set was analysed by conducting a mixed-model analysis of variance and panel regressions.Results: A high level of IRQ was found to be significantly associated with high levels of ESG performance, as well as high earnings per share and high leverage.Conclusion: It appears that IR strengthens managerial efficiency and legitimacy in the eyes of debt capital providers in South Africa, while equity capital providers do not provide a clear signal of approval.